Occurrence and antimicrobial susceptibility profile of Streptococcus canis isolates from cats and dogs - Mohd Hafiz Ngoo, Siti Aisyah; Yam, Melissa Khai Jie; Hassan, Murnihayati; Chan, Wei Yee; Ahmad, Nur Indah; Zakaria, Zunita; Than, Leslie Thian Lung; Ooi, Peck Toung; Selvarajah, Gayathri Thevi (2024)
Streptococcus canis (5. canis) is a normal flora normally found in oral mucosa and skin of cats and dogs, but various studies have shown that the pathogen is able to cause diseases in a wide range of animals and some clinical cases are severe enough to cause death. This study aimed to describe the occurrence of clinical cases of 5. canis, as well as phenotypic and antimicrobial susceptibility patterns in cats and dogs. Data was retrieved from the Bacteriology Laboratory of Faculty of Veterinary Medicine, Universiti Putra Malaysia. A retrospective analysis was conducted for data collected from January 2019 until December 2023. A total of 92 feline and 36 canine cases identified with 5. canis infections. For both cats and dogs, 5. canis were mainly isolated from pyogenic wounds, ear infections and multiple organ involvement. Antimicrobial susceptibility test (AST) done for cats and dogs showed 5. canis are highly susceptible to amoxicillin, amoxicillin-clavulanic acid and cephalosporin antibiotics. High antimicrobial resistance was seen in neomycin, metronidazole and polymyxin B, with resistance rates from 72% to 100%. One of the most used antibiotics, enrofloxacin, showed a low susceptibility rate of 30% and 26% for both cats and dogs respectively. Up to 57% of 5. canis in cats and dogs exhibit multidrug resistance. To conclude, 5. canis is an emerging and important pathogen in cats and dogs as it exhibits a high antimicrobial resistance pattern and are also capable of affecting different species as well. Further studies on drug resistance and therapeutic outcome of cats and dogs are reasonable.